Teaching Disciplines "History of Russia" and "Country Studies" to Foreign Students: Problems and Solutions; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Voytovich A. V. Aleksey Viktorovich (2015, 2015)
Title screen